(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Reconstruction for injuries around the ankle becomes a challenge due to limitation of available similar or near similar tissue. Tendons, bones and joints are frequently exposed after trauma because of the thinness of the subcutaneous tissue around the ankle. A durable flap with good texture, reliable vascularity, good arc of rotation and minimum donor site morbidity is always desired for coverage of such defect. Traditionally local flaps are used for resurfacing but their use is limited by their size and arc of rotation. This study was done in the dept. of Plastic Surgery, NITOR from Dec, 2012 to Feb, 2016. Total number of patients was 50 and their age varied from 7 years to 55 years. Among the 50 patients, 41 patients recovered uneventfully, 8 patients showed partial flap necrosis and complete flap necrosis in 1 patient. The distally based sural flap is a versatile and reliable flap for coverage of soft tissue defects around the ankle. Most of the cases were single stage procedure except extended reverse sural flap. The dissection is easy with short operative time and minimum morbidity. Thus the superficial sural artery flap can be used as a good alternative to microsurgical reconstruction. J Bangladesh Coll Phys Surg 2018; 36(3): 101-106